Using Moderator Analysis to Identify the First-Grade Children Who Benefit More and Less From a Reading Comprehension Program: A Step Toward Aptitude-by-Treatment Interaction. (January 2019) - Fuchs, Douglas; Kearns, Devin M.; Fuchs, Lynn S.; Elleman, Amy M.; Gilbert, Jennifer K.; Patton, Samuel; Peng, Peng; Compton, Donald L.
Because of the importance of teaching reading comprehension to struggling young readers and the infrequency with which it has been implemented and evaluated, we designed a comprehensive first-grade reading comprehension program. We conducted a component analysis of the program's decoding/fluency and reading comprehension dimensions (DF and COMP), creating DF and DF+COMP treatments to parse the value of COMP. Students ( N = 125) were randomly assigned to the two active treatments and controls. Treatment children were tutored three times per week for 21 weeks in 45-min sessions. Children in DF and DF+COMP together performed more strongly than controls on word reading and comprehension. However, pretreatment word reading appeared to moderate these results such that children with weaker beginning word reading across the treatments outperformed similarly low-performing controls to a significantly greater extent than treatment children with stronger beginning word reading outperformed comparable controls. DF+COMP children did not perform better than DF children. Study limitations and implications for research and practice are discussed.